KONDISI FATHERLESS SERTA REGULASI EMOSI REMAJA DI SEKOLAH MENENGAH ATAS NEGERI 2 LAIS - Surahman; Taty Fauzi; Ramtia (IKIP Siliwangi, 2026)
This study was motivated by the psychological and social conditions of adolescents at SMA Negeri 2 Lais who have grown up without the presence of a father figure. During adolescence, the absence of a father may affect the development of emotional regulation, causing students to experience difficulties in recognizing, managing, and controlling their emotions. This condition is characterized by excessive emotional reactions, difficulty controlling anger, a tendency to withdraw from social interactions, and decreased concentration in learning. The validity and reliability of the research instruments were tested using SPSS version 27.0. The reliability test results indicated high Cronbach's Alpha coefficients for both variables, namely 0.726 for the Fatherless variable and 0.938 for the Emotional Regulation variable, indicating that the instruments were reliable. The collected data were analyzed using descriptive statistics, prerequisite testing (normality test), and simple linear regression analysis to test the research hypothesis. The normality test was conducted using the Kolmogorov–Smirnov test at a significance level of 0.05 with SPSS version 27.0. The significance value obtained was 0.102 (> 0.05), indicating that the data met the assumption of normality. Correlation analysis was then performed using the Pearson Product-Moment correlation. The results showed a Pearson correlation coefficient of r = 0.023 with a p-value of 0.827 (> 0.05). Therefore, the null hypothesis was accepted, indicating that there was no significant correlation between the Fatherless and Emotional Regulation variables. These findings suggest that although students may perceive the emotional support role of a father, the relationship between fatherlessness and emotional regulation is extremely weak, as reflected by the correlation coefficient (r = 0.023), which is very close to zero.